Регенерированные твердосплавные смеси, полученные разными методами переработки техногенного сырья - Бондаренко, В.П.; Мартынова, Л.М.; Сытник, А.А.; Руденький, С.Г.; Гнатенко, И.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
The paper gives results of an investigation into chemical, X-ray diffraction and morfological characteristics of WC–6Co and WC–8Co regenerated cemented carbide mixtures prepared by the following methods of the reprocessing of man-caused raw materials in Ukraine: thermochemical, carbon black-free ("Alcon-Tverdosplav", Kiev) and zinc method ("Karma", Svetlovodsk, "Tekhnokor", Khar'kov). WC–6Co, WC–6Co (C) and WC–8Co serial mixtures ("KZTS", Russia) have been studied for comparison. It was found that characteristics of tungsten carbide and cobalt particles in the regenerated mixtures are not identical.